Patient-derived organoids in non-small cell lung cancer: advances in drug sensitivity testing - Tang, Wanyu; Tian, Xudong (Frontiers in Pharmacology, 2026)
Patient-derived organoids (PDOs) have emerged as transformative preclinical models in non-small cell lung cancer (NSCLC), offering high-fidelity recapitulation of tumor heterogeneity and drug responses. Compared to traditional cell lines and xenografts, PDOs preserve the genetic, phenotypic, and functional features of parental tumors, enabling precise drug sensitivity testing for chemotherapy, targeted therapy, and immunotherapy, particularly through optimized culture protocols, genetic engineering techniques, and cryopreservation methods, have significantly enhanced their scalability and clinical relevance. PDOs have proven instrumental in elucidating key resistance mechanisms such as EGFR-TKI resistance mediated through DCLK1-dependent Wnt signaling activation, while simultaneously identifying novel therapeutic synergies for clinical translatio. However, challenges remain in modeling the tumor immune microenvironment and standardizing clinical translation. This review systematically outlines the advancements and challenges in establishing NSCLC PDOs, highlights the potential of PDOs to guide personalized NSCLC therapy while addressing current limitations to bridge the gap between research and clinical application.